Comparison of the Effectiveness of Octenidine Dihydrochloride and Povidone-Iodine Antiseptics on Post-Circumcision Wound Healing Time - Muhammad Ardi Putrawardana; Ketut Holifah; Muhammad Alghifari Budiman; Fevi Padhila; Ratna Esmayanti; Herry Octa Winarto (GLOBAL HEALTH SCIENCE GROUP, 2026)
Circumcision is a minor surgical procedure that results in an acute incision wound and requires optimal care to prevent infection and accelerate epithelialization. Povidone-iodine has long been used as a standard antiseptic, but has been reported to have potential cytotoxicity against fibroblast cells. Octenidine dihydrochloride is an alternative antiseptic with high antimicrobial efficacy and better biocompatibility. This study aims to compare the effectiveness of both antiseptics on post-circumcision wound healing time. The study used a prospective parallel randomized controlled trial (RCT) design at the Darul Khitan Clinic in Bogor City with 34 pediatric patients randomized into two groups (n = 17). The intervention group received octenidine dihydrochloride, while the control group received povidone-iodine. Wound healing was assessed on days 3 and 7 using the WINNER Scale. Data were collected through direct observation and wound assessment by trained healthcare personnel using a standardized observation form. The data were analyzed using an independent t-test (p<0.05). The results showed that the mean wound healing score of the octenidine group was higher than that of povidone-iodine (9.59±1.37 vs 7.29±1.96) with a significant difference (p<0.001; 95% CI -3.482 to -1.106). It was concluded that octenidine dihydrochloride was more effective in accelerating post-circumcision wound healing than povidone-iodine and could be considered as a more optimal antiseptic choice in clinical practice.